DEVELOPING AREA-BASED COLLABORATION NETWORKS IN COMMUNITY FOR SUSTAINABLY BUILDING UP CIVIC CONSCIOUSNESS OF MULTICULTURALIS, CHANA DISTRICT, SONGKHLA - Suwanno, Pitchaya; Suksang, Saisuda; Churak, Yuwanda; Boonrat, Arisra; Aeksaitharn, Chittaphon (Journal of MCU Nakhondhat, 2025)
This research aimed to: 1) Examine the factors contributing to the development of a community-participated spatial collaboration network, and 2) Propose a framework for developing mechanisms to drive a community-participated multicultural social network that fosters citizenship awareness in Chana District, Songkhla Province, through the application of the Nathap Model. The target group consisted of 60 participants from Chanong and Talingchan Subdistricts in Chana District. A semi-structured interview protocol was employed to collect qualitative data. The findings revealed several key factors supporting the development of mechanisms to drive multicultural social networks with community participation in Chana District: 1) Executives of government agencies played a vital role in promoting and supporting activities that reflected community identity; 2) These executives emphasized the importance of establishing cooperative networks within specific community groups under their jurisdiction; 3) Community members actively participated in various collaborative activities; 4) Community representatives demonstrated strong leadership potential and effectively coordinated with local leaders; and 5) While community-based networks operated for social benefit, they tended to act independently. The brainstorming sessions conducted using the Nathap Model contributed to the development of a comprehensive framework for establishing mechanisms to sustain a multicultural social network through community participation. The community proposed a range of participatory activities designed to promote multicultural understanding and shared civic engagement. These activities included: Elderly Day Celebrations, Singing, Dancing, Cooking, and Reminiscing Events, Eat, Shop, and Engage Initiatives, Fun Housewives’ Group Activities, Walking Events from Talingchan Beach to Chanong Beach, and Institution-Community Relationship-Building Programs. All activities were framed within the conceptual foundation of multicultural engagement to enhance social cohesion and intercultural understanding within the community.